Gambaran Kadar Bilirubin Total pada Penderita Tuberkulosis Paru dengan Terapi Obat Anti Tuberkulosis (Oat) di Puskesmas Poasia Kota Kendari - Firdayanti Firdayanti (Sekolah Vokasi Universitas Gadjah Mada, 2019)
Background: Treatment of tuberculosis by using anti-tuberculosis drugs (OAT) can be accepted in therapy, but has potential effectiveness such as side effects of hematologic reactions, namely anemia, agranulocytosis, eosinophilia and thrombocytopenia, and liver function. Hyperbilirubinemia is one of the side effects of using OAT which is often complained by patients.Objective: to determine the description of total bilirubin levels in tuberculosis patients with OAT therapy at the Poasia Health Center in Kendari CityMethod: This study was descriptive with bilirubin examination using the Jendrassik-Grof method by spectrophotometer. Total bilirubin examination was performed on 18 pulmonary tuberculosis patients who received OAT therapy at the Poasia Health Center in Kendari City.Results: The results of the study showed that from 18 samples examined, there were 10 samples with high bilirubin levels (hyperbilirubinemia) and 8 samples had normal bilirubin levels.Conclusion: Total bilirubin levels in patients with pulmonary tuberculosis with OAT therapy were found as many as 10 patients had high bilirubin levels (hyperbilirubinemia) and 8 patients had normal bilirubin levels. Keywords: Bilirubin, Hyperbilirubinemia, OAT, Therapy, Tuberculosis